A Case Study Of Procurement Of Christian Education Teacher In Public Elementary School In Sub-District Of Candisari Of Semarang - Surja Permana (IJEBD (International Journal of Entrepreneurship and Business Development), 2017)
Purpose : The purpose of this research was to know the reasons or causes of lack or absence of Christian Education teachers Design/methodology/approach : The method used in this research was explorative-descriptive case study. Case study procedure in this research had four stages: description (observing/studying), analysis (trying to understand), interpretation (interpretation of data), and action (action plan based on the result of research data). Findings : the main obstacle to procurement of Christian Education teachers as Non-Permanent Teachers was lack or absence of budget Research limitations/implications : This study was limited to the number of Christian students. Interview means that the researcher asked questions to school administrators to obtain information according to research variables. To complete the information required, the researcher observed on the implementation of Christian Education at Public Elementary School in Sub-district of Candisari, Semarang. Practical implications : First, in Sub-district of Candisari there were 37 Public Elementary Schools. Thirty-six schools had Christian students. There were only six Christian Education teachers who teaching Christian Education at 16 schools. Six Christian Education teachers for 16 schools, mean 43% of schools had teachers who teaching Christian Education. That mean 57% or 20 Public Elementary Schools in Sub-district of Candisari had no Christian Education teachers. Originality/value : the Government or the school administrators were less concerned with the implementation of Christian Education, then the church (Christian community) must be willing to assume the responsibility by sending and financing Christian Education teachers to schools that did not have Christian Education teachers yet